Unique Electronic Structure in a Porous Ga‐In Bimetallic Oxide Nano‐Photocatalyst with Atomically Thin Pore Walls. (16th August 2016) - Chen, Hui; Yu, Guangtao; Li, Guo‐Dong; Xie, Tengfeng; Sun, Yuanhui; Liu, Jingwei; Li, Hui; Huang, Xuri; Wang, Dejun; Asefa, Tewodros; Chen, Wei; Zou, Xiaoxin
Abstract: A facile synthetic route is presented that produces a porous Ga‐In bimetallic oxide nanophotocatalyst with atomically thin pore walls. The material has an unprecedented electronic structure arising from its ultrathin walls. The bottom of the conduction band and the top of the valence band of the material are distributed on two opposite surfaces separated with a small electrostatic potential difference. This not only shortens the distance by which the photogenerated charges travel from the sites where they are generated to the sites where they catalyze the reactions, but also facilitates charge separations in the material. The porous structure within the walls results in a large density of exposed surface reactive/catalytic sites. Because of these optimized electronic and surface structures, the material exhibits superior photocatalytic activity toward the hydrogen evolution reaction (HER).